Dual aVß8 Integrin and PD-1 Blockade Overcomes TGFβ-Mediated B-Cell Suppression to Enhance Anti-Tumor Immunity - Hou, David; Wang, Si; Castro, Brandyn A.; Katz, Joshua L.; Dapash, Mark; Arrieta, Victor A.; Vazquez-Cervantes, Gustavo I.; Wan, Hanxiao; Billingham, Leah K.; Du, Rebecca; Murphy, Alina R.; Lopez-Rosas, Aurora; et al. (Neuro-Oncology, 2025)
Background. Immunotherapy has revolutionized cancer treatment but has yet to be translated into brain tumors. Studies in other solid tumors suggest a central role of B-cell immunity in driving immune checkpoint blockade efficacy. In glioblastoma (GBM), tumor B cells are driven into a regulatory B-cell state that suppresses immune activation and T-cell function. Methods. We used spatially resolved transcriptomics and multiplex immunofluorescence to characterize B-cell neighborhoods within GBM and identify enhanced TGFβ-signaling between myeloid and B cells. We generated conditional knockouts to investigate the effects of TGFβ signaling on B-cell function and survival in vivo. Additionally, we combined TGFβ blockade with PD-1 inhibition to evaluate their combined anti-glioma efficacy. Results. Our findings reveal that myeloid cells are the primary interactors with B cells in GBM through the TGFβ pathway. Pharmacological or genetic TGFβ blockade expanded intratumoral B cells and synergized with PD-1 inhibition to enhance survival (60% tumor eradication in dual-treated mice). Therapeutic efficacy critically depended on B cells, as their depletion abolished survival benefits. Dual αVβ8/PD-1 blockade reduced B-cell-mediated suppression of CD8⁺ T-cell cytotoxicity and increased plasmablast differentiation, while partial efficacy in RagKO mice implicated ancillary roles for innate immunity. Conclusion. Targeting TGFβ signaling using an anti-αVβ8 blocker can impact anti-tumor immunity through different possible mechanisms, of which we highlight the rescuing of B-cell function through synergy with PD-1 checkpoint blockade therapy. Our work underscores the critical role of intratumoral B-cell immunity in enhancing immunotherapy against brain tumors.
CRIS-Team Scopus Importer:2025-10-31
Keywords: B cells; checkpoint-blockade; glioblastoma; TGFβ; tumor microenvironment